AKUNTABILITAS PENGELOLAAN KEUANGAN DESA TAHUN ANGGARAN 2015 DI KECAMATAN SINTANG KABUPATEN SINTANG - B2053151013, AGUS FRAYUDHA (Jurnal Ekonomi Daerah (JEDA), 2017)
This study describes and analyzes the accountability of village financial management of the fiscal year 2015 based on The Minister of Home Affairs Regulation No. 113 of 2014 in 13 villages in the district of Sintang. The method used is descriptive qualitative approach. Collecting data using questionnaires, interviews, and documents. Data analysis using comparative analysis,flowchart analysis, and document analysis with Miles and Hubermann approach. The results showed that the implementation of the principle of accountability of the planning phase has been implemented five village, the implementation phase of 7 villages, 13 villages stage of administration, and the stage of reporting and accountability 5 villages. Results of research to average proportion of personnel expenditure and expenditure fields in APBDesa indicate that the average proportion of personnel expenditure and sectors expenditure are in accordance with Government Regulation No. 43 of 2014. Keywords: Accountability, The Minister of Home Affairs Regulation No. 113 of 2014, the management of village finances.